UUM student perception on the use of job search website in Malaysia - Romli, Azizi; Hassan, Mohamad Ghozali; Mohtar, Shahimi; Ramli, Azahari (2012)
Nowadays, we can found many job search website in the internet.An online job search is also highly convenient. For instance, the people can post the resume on a job-oriented website and it might find corporate head-hunters that will flock to the personal e-mail inbox. Beside this, job searching offered limited job titles and little detail about the work.This report will explain about the UUM students' perception on the use of job search website in Malaysia and the user interface of satisfactions. Furthermore, the conceptual framework which attempts to operate in this study is Technology Acceptance Model, SERVQUAL and Customer Satisfaction.